2003
DOI: 10.1080/14017430310015505
|View full text |Cite
|
Sign up to set email alerts
|

Electroanatomic mapping of transseptal conduction during coronary sinus pacing in patients with paroxysmal atrial fibrillation

Abstract: During distal CS pacing, a preferential site of transseptal conduction near the CS ostium was demonstrated in patients with paroxysmal AF. This has clinical implications when surgical dissection or catheter ablation is considered to eliminate interatrial connection in patients with AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In the present study, the activation velocities of cross-CSo and intra-CS during distal CS pacing were measured. These measurements should represent the actual conduction velocities since the preferential conduction route during distal CS pacing is along the long axis of the CS as observed previously (9,17) (Fig 3). We found that the activation velocities of intra-CS were similar in the two groups, whereas the cross-CSo activation velocities in the AF group appeared slower than those in the control group.…”
Section: Deterioration Of Interatrial Conduction During Distal Cs Pacmentioning
confidence: 88%
See 2 more Smart Citations
“…In the present study, the activation velocities of cross-CSo and intra-CS during distal CS pacing were measured. These measurements should represent the actual conduction velocities since the preferential conduction route during distal CS pacing is along the long axis of the CS as observed previously (9,17) (Fig 3). We found that the activation velocities of intra-CS were similar in the two groups, whereas the cross-CSo activation velocities in the AF group appeared slower than those in the control group.…”
Section: Deterioration Of Interatrial Conduction During Distal Cs Pacmentioning
confidence: 88%
“…Using the CARTO mapping system, different activation patterns of the right atrium during pacing from the distal CS have been observed, with most right atria presenting a single transseptal breakthrough near the CS ostium (9,17). In addition, using the Ensite 3000 noncontact mapping system, O'Donnell et al observed similar preferential inter-atrial conduction route during pacing in the left upper pulmonary vein (3).…”
Section: Deterioration Of Interatrial Conduction During Distal Cs Pacmentioning
confidence: 99%
See 1 more Smart Citation
“…5,15,19 Therefore, conceivably the CS may play a major role in the interatrial electrical connection during ATs originating from the lateral LA and left PVs that are close to the distal CS. In the present study, RA breakthrough sites at the CS ostium was found in one MA tachycardia and one tachycardia from inferoposterior LA but in none of the three left PV tachycardias having biatrial electroanatomic maps.…”
Section: Interatrial Electrical Propagationmentioning
confidence: 99%